A PUBLICIST DISCOURSE OF THE ISLAMIC ORGANIZATIONS OF THE CENTRAL FEDERAL DISTRICT OF RUSSIA AND THE ISSUE OF TOLERANCE - SEIDINA, Moldir; KARABULATOVA, Irina; POLIVARA, Zinaida; ZINCHENKO, Anastasia (CENTRAL ASIA AND THE CAUCASUS, 2017)
Today, the publicist discourse is best described as a polyvariant space of an interaction of linguistic and non-linguistic factors that determine the use of words and styles and their functioning. Special attention should be paid to the addressees as active interpreters of electronic and printed publicist texts and to the “conflicting text” concept interpreted in the context of negative realization of the usual-stylistic complex. The necessity of the problem discussed is determined by the new tasks related to the texts and recently formulated by contemporary science, since the traditional paradigm, based on the mode of obligation, has been replaced with a new, post-modernist one, based on the mode of possibility. This global change presupposes an interest in the contemporary publicist discourse of Islamic organizations in the context of confrontation of the Christian and Islamic worlds. Externally, the media have arrived at a new level of subjects and presentation; internally, they are functioning at a new linguistic level. Today, the mass media shook off their former ideological and official biases and taboos on particular subjects, while information sources became more numerous and more varied. In the last few years, the world of the media has changed structurally and economically; it relies on different sources of funding and looks different. Digital newspapers and information agencies can be described as a new element, which is steadily widening its audiences; they are determined to finally outdo the TV, especially where the speed of the delivery of news is concerned. So far, neither the interested structures of state power nor the expert community have offered a more or less adequate concept of confessional politics. The subject of our studies is further made germane by the need to identify the mechanisms and technologies of politicization of Islam to offer new ways and means of ensuring social and state security. The authors who investigate the ways ethnoconfessional conflicts are effected concentrate on the institutional discourses and actors (the academic and political circles and the media) and tend to ignore the space of electronic mass media that publish online discussions of their readers, the de facto independent level of constructing social conflicts.